2014
DOI: 10.1098/rstb.2013.0147
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitter receptor and time dependence of the synaptic plasticity disrupting actions of Alzheimer's disease Aβ in vivo

Abstract: Many endogenous factors influence the time course and extent of the detrimental effects of amyloid β-protein (Aβ) on synaptic function. Here, we assessed the impact of varying endogenous glutamatergic and cholinergic transmission by pharmacological means on the disruption of plasticity at hippocampal CA3-to-CA1 synapses in the anaesthetized rat. NMDA receptors (NMDARs) are considered critical in mediating Aβ-induced inhibition of long-term potentiation (LTP). However, intracerebroventricular injection of Aβ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 58 publications
2
25
1
Order By: Relevance
“…On the basis of multiple lines of evidence, soluble Aβ peptides are still regarded by many as key pathological species in AD, potentially contributing to both pathogenesis and disease progression (Hardy and Selkoe, ; Hardy and Higgins, ). Thus, in attempts to better understand the patho‐physiological mechanisms underlying AD, numerous studies focusing on the biological actions of acutely administered exogenous soluble Aβ peptides have been made both in vivo (An et al, ; Brouillette et al, ; Klyubin et al, ) and in vitro (Lambert et al, ; Lauren et al, ; Li et al, ; Minkeviciene et al, ; Parameshwaran et al, ; Puzzo et al, ; Wang et al, ). The other major approach to understanding Aβ biology focuses on the use of mouse lines transgenically engineered to overproduce Aβ peptide species, a model of more chronic exposure to Aβ species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of multiple lines of evidence, soluble Aβ peptides are still regarded by many as key pathological species in AD, potentially contributing to both pathogenesis and disease progression (Hardy and Selkoe, ; Hardy and Higgins, ). Thus, in attempts to better understand the patho‐physiological mechanisms underlying AD, numerous studies focusing on the biological actions of acutely administered exogenous soluble Aβ peptides have been made both in vivo (An et al, ; Brouillette et al, ; Klyubin et al, ) and in vitro (Lambert et al, ; Lauren et al, ; Li et al, ; Minkeviciene et al, ; Parameshwaran et al, ; Puzzo et al, ; Wang et al, ). The other major approach to understanding Aβ biology focuses on the use of mouse lines transgenically engineered to overproduce Aβ peptide species, a model of more chronic exposure to Aβ species.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the inhibition of long‐term potentiation is reported to require less than 1 h of Aβ pre‐treatment and maybe as little as 10 min in vivo (Cullen et al, ); indeed this group, who are perhaps the most prolific investigators of Aβ and hippocampal synaptic plasticity, use a standard treatment time in vivo of 15 mins. Also with regard to the time‐course of action of exogenous Aβ it has also been reported that a single in vivo injection can inhibit induction of synaptic plasticity 7 days later (Klyubin et al, ). Our experiments used what has been perhaps the most commonly used concentration of exogenous Aβ for in vitro studies of brain slices, namely 500 n M .…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological Techniques-In vivo electrophysiology was performed using techniques described previously (26). Animal experiments were licensed by the Department of Health and Children, Ireland.…”
Section: Methodsmentioning
confidence: 99%
“…After high‐frequency stimulation (the second hour) a rather significant increase (up to 180%) is shown. Although the error bars after high‐frequency stimulation are large (the red line) the high level of error bars is normal after HFS in in vivo electrophysiological experiments …”
Section: Resultsmentioning
confidence: 99%